2020
DOI: 10.1155/2020/1341326
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Predictive Powers for Mortality between Systemic Vascular Resistance Index and Serum Lactate in Children with Persistent Catecholamine‐Resistant Shock

Abstract: Persistent catecholamine-resistant shock in children causes severe morbidity and mortality. We aimed to analyze the association between hemodynamics and serum lactate at different time points and 28-day mortality in children with persistent catecholamine-resistant shock. Methods. Twenty-six children with persistent catecholamine-resistant shock were enrolled, and their hemodynamics were monitored using the pulse index continuous cardiac output. Serial cardiac index (CI), systemic vascular resistant index (SVRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Previous reports have shown that lower SVRI is associated with mortality in adults with septic shock [20,21]; however, the clinical utilization of SVRI has not been well surveyed in pediatric septic shock. Our previous study with the same group reported that SVRI was a predictor for in-hospital mortality in pediatric septic shock [22]. The current study was an expansion of the previous one, which demonstrated the importance of SVRI in the different time points of pediatric septic shock.…”
Section: Discussionsupporting
confidence: 58%
“…Previous reports have shown that lower SVRI is associated with mortality in adults with septic shock [20,21]; however, the clinical utilization of SVRI has not been well surveyed in pediatric septic shock. Our previous study with the same group reported that SVRI was a predictor for in-hospital mortality in pediatric septic shock [22]. The current study was an expansion of the previous one, which demonstrated the importance of SVRI in the different time points of pediatric septic shock.…”
Section: Discussionsupporting
confidence: 58%
“…1 ). 23 26 27 28 29 30 31 32 33 34 35 36 Of these 12 studies, 4 (33%) included patients after cardiac surgery, 3 (25%) included patients with shock, and the remainder included patients with various diagnoses. Out of the 2,099 patients, 357 (17%) experienced mortality.…”
Section: Resultsmentioning
confidence: 99%